The upholding of multilateralism idea and the efforts done by stakeholders - Sabar, Rohafiz; Chan, Jia Min; Oh, Chai Ying; Goh, Li Wen (2012)
Multilateralism is the practice of promoting trade among several countries through agreements concerning quantity and price of commodities, as the Common Market, and sometimes, restrictive tariffs and goods from outsiders. In this paper, the difference of perception between the Westerns and the Asians on the idea of multilateralism would be looked into in details.Also, this paper highlighted a few points that include the relationship between the stakeholders and the force driving the upholding of multilateralism. Information on this topic are gathered by doing research on published and unpublished materials that dated back to the early formation of the idea so as to support the reliability of this research. In a nutshell, this research paper is highly informative in the field of multilateralism.